Undamped Higgs Modes in Strongly Interacting Superconductors - José Lorenzana; Götz Seibold (Condensed Matter)
In superconductors, gauge <semantics>U(1)</semantics> symmetry is spontaneously broken. According to Goldstone’s theorem, this breaking of a continuous symmetry establishes the existence of the Bogoliubov phase mode while the gauge-invariant response also includes the amplitude fluctuations of the order parameter. The latter, which are also termed ‘Higgs’ modes in analogy with the standard model, appear at the energy of the spectral gap <semantics>2Δ</semantics>, when the superconducting ground state is evaluated within the weak-coupling BCS theory, and, therefore, are damped. Previously, we have shown that, within the time-dependent Gutzwiller approximation (TDGA), Higgs modes appear inside the gap with a finite binding energy relative to the quasiparticle continuum. Here, we show that the binding energy of the Higgs mode becomes exponentially small in the weak-coupling limit converging to the BCS solution. On the other hand, well-defined undamped amplitude modes exist in strongly coupled superconductors when the interaction energy becomes of the order of the bandwidth.